Appreciate but not Acknowledge: (State Construction Towards Religion and Regulations with Discriminatory Nuances) - Indara, Rona; Mantu, Rahman (Aqlam: Journal of Islam and Plurality, 2024)
Abstract: The meaning and recognition of religions in Indonesia are closely related to politics. Political sentiment during the transition of power from the old order to the new order affects how the State interprets religion in the constitution. Especially during the New Order period, minority religions or beliefs received discriminatory treatment, this fact was evidenced by various regulations that were impartial and protected minority religions and until now these policies continue to be used. The state, in this case, the government is intensively campaigning for the idea and practice of diversity, tolerance, and religious moderation, along with which there are many cases of violence and discrimination based on religious backgrounds. Using a socio-juridical approach, the author then found many regulations related to religion and beliefs that are still discriminatory and do not protect all citizens of the nation, as mandated by the 1945 Constitution.Keywords: Religion, Regulation, Discrimination, Diversity, Government.Abstrak : Pemaknaan dan pengakuan Agama-agama di Indonesia sangat berkait erat dengan Politik. Sentimen politik saat peralihan kekuasaan dari orde lama ke orde baru berpengaruh terhadap bagaimana Negara memaknai Agama di dalam konstitusi. Terlebih di masa Orde baru agama atau kepercayaan minoritas mendapatkan perlakuan yang diskriminatif, fakta itu dibuktikan dengan berbagai macam regulasi yang tidak berpihak dan melindungi agama minoritas dan sampai sekarang kebijakan-kebijakan tersebut terus digunakan. Negara dalam hal ini pemerintah sedang gencar mengkampanyekan gagasan dan praktik kebhinekaan, toleransi, serta moderasi beragama, seiring dengan itu muncul banyak kasus kekerasan dan diskriminasi berlatar belakang agama. Dengan menggunakan pendekatan sosio-yuridis penulis kemudian menemukan Â banyak regulasi-regulasi berkaitan dengan agama dan kepercayaan yang masih bernuansa diskriminatif dan tidak melindungi segenap warga bangsa, sebagaimana amanat UUD 1945.Kata Kunci: Agama, Regulasi, Diskriminatif, Kebhinekaan, Pemerintah.